2013
DOI: 10.1038/srep02615
|View full text |Cite
|
Sign up to set email alerts
|

The ClC-3 chloride channel associated with microtubules is a target of paclitaxel in its induced-apoptosis

Abstract: Recent evidences show that cationic fluxes play a pivotal role in cell apoptosis. In this study, the roles of Cl− channels in paclitaxel-induced apoptosis were investigated in nasopharyngeal carcinoma CNE-2Z cells. Chloride current and apoptosis were induced by paclitaxel and inhibited by chloride channel blockers. Paclitaxel-activated current possessed similar properties to volume-activated chloride current. After ClC-3 was knocked-down by ClC-3-siRNA, hypotonicity-activated and paclitaxel-induced chloride cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…It has been confirmed by our previous work the swellingactivated currents in CNE-2Z cells are through ClC-3 (Zhang et al, 2013a;Zhu et al, 2012). Whether the swelling-independent currents induced by glycerol are via ClC-3 was investigated.…”
Section: Chloride Channel Activation By Extracellular Glycerolsupporting
confidence: 63%
See 1 more Smart Citation
“…It has been confirmed by our previous work the swellingactivated currents in CNE-2Z cells are through ClC-3 (Zhang et al, 2013a;Zhu et al, 2012). Whether the swelling-independent currents induced by glycerol are via ClC-3 was investigated.…”
Section: Chloride Channel Activation By Extracellular Glycerolsupporting
confidence: 63%
“…ClC-3, a member of the voltage-gated chloride channel family, shows the properties of cell cycle-dependent expression and subcellular distribution, and plays an important role in the regulation of cell proliferation, migration and apoptosis, especially in cancerous cells (Hong et al, 2015;Liu et al, 2013;Mao et al, 2012Mao et al, , 2013Xu et al, 2014;Zhang et al, 2013a). The inducible ClC-3 gene deletion eliminating native VRAC in adult mice overwhelmingly suggested that ClC-3 is a key component of native VRAC in mammalian heart, not in the brain (Xiong et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…We and others have shown that ClC-3, a candidate of volumesensitive Cl − channels, is the main chloride channel protein mediating the cell volume changes associated with proliferation, migration and apoptosis (Chen et al, 2002;Mao et al, 2008Mao et al, , 2009Mao et al, , 2012Mao et al, , 2013Zhang et al, 2013a;Zhang et al, 2013b;Zhu et al, 2012). We demonstrated previously that lithium could inhibit the swelling-induced Cl − current (I Cl,swell ) in nasopharyngeal carcinoma cells (Bai et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…However, microtubules play a fundamental role not only in the mitosis but also in form the cell cytoskeleton. Previous studies have demonstrated that the changes of cytosolic Cl - concentration trigger microtubule remodeling and thereby affects intracellular vesicle trafficking in LLC-PK 1 renal proximal tubule-like cell [62] and that the application of PTX induces transmembrane Cl - current and apoptosis in nasopharyngeal carcinoma CNE-2Z cells via upregulation of ClC-3 Cl - channel expression and its accumulation in cell membrane; ClC-3 Cl - channels are co-localized with membrane microtubules [63]. Consequently, it is possible that PTX would affect tumor cell proliferation not only via the mitotic spindle defects but also by the Cl - -dependent remodeling of the microtubule cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%